Active and adaptive plasticity in a changing climate. (July 2022) - Brooker, Rob; Brown, Lawrie K.; George, Timothy S.; Pakeman, Robin J.; Palmer, Sarah; Ramsay, Luke; Schöb, Christian; Schurch, Nicholas; Wilkinson, Mike J.
Abstract : Better understanding of the mechanistic basis of plant plasticity will enhance efforts to breed crops resilient to predicted climate change. However, complexity in plasticity's conceptualisation and measurement may hinder fruitful crossover of concepts between disciplines that would enable such advances. We argue active adaptive plasticity is particularly important in shaping the fitness of wild plants, representing the first line of a plant's defence to environmental change. Here, we define how this concept may be applied to crop breeding, suggest appropriate approaches to measure it in crops, and propose a refocussing on active adaptive plasticity to enhance crop resilience. We also discuss how the same concept may have wider utility, such as in ex situ plant conservation and reintroductions. Highlights: Increasing environmental uncertainty is focussing research interest on plant plasticity. But despite calls for plasticity concepts to be adopted in crop breeding, this does not appear to have happened. Plasticity is a broad and multifaceted concept, making it potentially difficult to identify those aspects of previous research most relevant to the crop breeding context. Given the challenges posed by climate change and the different evolutionary contexts in natural and crop systems, we identify active adaptive plasticity as a key issue for further investigation by crop breeders. We outline and illustrate the experimental and statistical analytical approaches necessary to begin to assess active adaptive plasticity, and we highlight benefits that might arise in other fields from a fuller understanding of the role and regulation of this aspect of plasticity.